The Alignment of Target Cost and Cost System Based on Time-Driven Activities (TD-ABC) and its Impact on the Development of Production Processes (An Applied Study in a Sample of Iraqi Industrial Companies) - Ghassan Ali Al-Abadi (Journal of Madenat Alelem University College, 2021)
The aim of the research is to find out the role of the correlation between the cost system based on time-oriented activities (TD-ABC) and the target cost system in the development of production processes in the Iraqi industrial companies. In order to achieve this objective, the research was applied to a sample of Iraqi industrial companies, South / Samawah Cement Factory.        The main objective of the research is that the implementation of the target cost system gave a comprehensive explanation of the Samawah Cement Factory about the desired costs of spending and the actual costs and the extent of the company's ability to achieve abundance in order to reduce costs and achieve profits as well as contribute to the implementation of the system (TD-ABC) determination of the unused energy in the production sections of Samawah Cement Factory in order to achieve the low cost which is reflected in the profits due to the low cost.         The most important thing recommended by the research is the need to interest Iraqi industrial companies to apply fair systems in the distribution of costs and organization of activities in a manner that reduces costs and reduces the waste resources, as well as the need to adopt the Iraqi industrial companies to regulate the distribution of costs on activities to achieve accuracy in determining the cost of one unit.